A novel causative gene variant, TNFRSF13B p.Gly76Ser, in patients with pulmonary arterial hypertension. (25th November 2020) - Shinya, Y; Hiraide, T; Kataoka, M; Momoi, M; Goto, S; Katsumata, Y; Endo, J; Sano, M; Kosaki, K; Fukuda, K
Abstract: Background: Pulmonary artery hypertension (PAH) is a poor prognostic disease. Some causative genes were reported as the PAH-associated genes. However, the pathogenetic variants in PAH-associated genes have not been identified in majority of patients with idiopathic PAH. Purpose: Our aim was to investigate the new causative gene variants associated with PAH. Methods: We performed whole-exome sequencing in 272 patients with idiopathic/heritable PAH. Structural analysis simulation was performed to define how the candidate gene variant affected the structure of protein. Results: We identified the heterozygous substitution change of c.226G>A (p.Gly76Ser, rs146436713) in tumor necrotic factor receptor superfamily 13B gene (TNFRSF13B) (NM_012452.2) in 6 (2.2%) patients with idiopathic/heritable PAH, although the allele frequency of this rare variant is 0% in Integrative Japanese Genome Variation Database (control population database). Two of the six cases were blood relatives, although they did not have the known causative gene variants of PAH. One of these two relatives died of right heart failure despite the combination medical therapy, and her pathological anatomy demonstrated intimal thickening and medial hypertrophy in the pulmonary arteries, formation of plexiform lesions (Heath-Edwards classification grade V). Time-lapse images from structural analysis simulation showed the instability of N-terminal in the protein, which regulates the vascular inflammation, synthesized from TNFRSF13B p.Gly76Ser variant (Figure), suggesting that p.Gly76Ser variant may be involved in the development of PAH via aberrant inflammation in pulmonary vessels. Conclusions: TNFRSF13B p.Gly76Ser variant is a candidate of causative gene variant for PAH. Funding Acknowledgement: Type of funding source: None